2005
DOI: 10.2337/diabetes.54.1.228
|View full text |Cite
|
Sign up to set email alerts
|

Altered Transcapillary Escape of Albumin and Microalbuminuria Reflects Two Different Pathogenetic Mechanisms

Abstract: We studied the following in normo-and microalbuminuric hypertensive type 2 diabetic patients: 1) transcapillary escape rate of albumin (TERalb) and 2) expression of mRNA slit diaphragm and podocyte proteins in renal biopsies. Normoalbuminuric subjects had renal cancer, and kidney biopsy was performed during surgery. TERalb was evaluated by clearance of 125 Ialbumin. Real-time PCR of mRNA slit diaphragm was measured in kidney specimens. Albumin excretion rate (AER) was by definition lower in normoalbuminuric su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…This has been demonstrated by Adler et al (29) and by our research group (11), who showed in microalbuminuria altered mRNA expression of several glomerular proteins.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This has been demonstrated by Adler et al (29) and by our research group (11), who showed in microalbuminuria altered mRNA expression of several glomerular proteins.…”
Section: Discussionsupporting
confidence: 78%
“…The patterns of renal lesions in the 157 type 2 diabetic patients with hypertension and microalbuminuria were classified as described previously using light microscopy technique by A.S. and R.F. (4,11,25,26), who were unaware of the clinical features of the patients as follows. Category 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alpha actinin 4 is not a slit diaphragm protein per se, but is located in the vicinity of the slit diaphragm in the cytoskeleton of the podocyte foot process [5]. Interestingly, the alpha actinin 4 mRNA is underexpressed in the glomeruli of patients with microalbuminuria compared with patients with normal AER [10]. In addition, a combination of glucose and advanced glycation end-products reduced the expression of alpha actinin-4 at both the protein and the Table 1 c Patients homozygous for the minor allele (2/2) were compared with patients homozygous for the major allele (1/1) d The non-synonymous R229Q SNP in NPHS2 characterised by Tsukaguchi et al [13] was included mRNA level in podocytes in vitro [11].…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] It has been suggested that albuminuria not only reflects glomerular damage, but also is a sensitive indicator of generalized endothelial dysfunction and capillary vasculopathy that leads to penetration of atherosclerotic lipoproteins into the arterial walls. [24][25][26] Although albuminuria is associated with endothelial dysfunction in systemic circulation, 26 the mechanism for this association remains unclear.…”
Section: Albuminuria and Endothelial Dysfunctionmentioning
confidence: 99%